How bilingual experience and executive control influence development in language control among bilingual children. Issue 1 (21st June 2019) - Kubota, Maki; Chevalier, Nicolas; Sorace, Antonella
Abstract: This longitudinal study investigates whether the development in executive control and bilingual experience predicts change in language control in bilingual children. Children were tested twice over the course of 1 year, using the language‐switching paradigm and the Simon task. The participants were Japanese‐English bilingual "returnee" children (ages 7–13), who returned to their first language (L1) environment after spending some years in a second language (L2) dominant environment. Testing these children upon their return to the L1 environment allowed us to disentangle the effect of age from bilingual experience, as they experienced an increase in age but a decrease in L2 exposure over time. Children who had less L2 exposure showed smaller improvement in baseline performance when naming pictures in English (i.e., when English was relevant across all trials). Moreover, development in trials where children had to switch between languages were modulated by development in executive control. That is, children who increased their performance in the English mixed repetition trials also performed better on the executive control task over time. Thus, development in executive control modulated change in language control among bilingual children, suggesting a positive relationship between language control and executive control in children's development. Abstract : Language control development in bilingual children, measured through the language switching paradigm, was modulated by both the amount of language exposure and improvement in executive control. Children who received more second language exposure and better developed their executive control performances showed greater improvement in naming pictures in their L2.